Strategi Peningkatan Kinerja Manajemen Keuangan dan Non Keuangan: Pendekatan Balance Scorecard - Gifta Khairul Nisa; Dyah Ani Pangastuti; Parawijati Parawijati (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
This study aims to describe the performance of school-based financial and non-financial management using a balanced scorecard approach. This research focuses on the public sector which describes the performance at SMK Al-Fattah Kalitidu, Bojonegoro Regency, East Java. The method used is a quantitative descriptive. The sample in this study amounted to 112 respondents. The analytical tool used in this study uses SPSS software. The results of the study show that the performance of the financial perspective at Al-Fattah Kalitidu Vocational School in the 2021-2022 academic year is quite economical, quite efficient, and very effective. The customer aspect also shows that SMK Al-Fattah Kalitidu is in the very good category. While the internal business perspective includes two aspects, namely the aspect of innovation is in the very good category and after-sales service is in the good category. Also from a learning and growth perspective, Al-Fattah Kalitidu Vocational School is in a very satisfying category. This research provides an understanding of school success in managing financial aspects, customer service, internal business, and student learning and growth.